Providers, Peers and Patients: How do Physicians' Practice Environments Affect Patient Outcomes? - Daniel Avdic; Maryna Ivets; Bo Lagerqvist; Ieva Sriubaite (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
We study the extent to which physician treatment styles are determined by their practice environment and whether such decisions affect the quality of care received by patients. Using rich data on all coronary angioplasty procedures in Sweden 2004–2013, our empirical approach compares stent choices of interventional cardiologists moving across hospitals to patient outcomes over time. To disentangle changes in practice styles attributable to physical (provider) and social (peer group) factors, we exploit quasi-random variation on physicians working on the same day in the same hospital. Our findings suggest that (i) moving cardiologists' stent choices rapidly adapt to their new practice environment after relocation; (ii) practice style changes are equally driven by the physical and social environments; and (iii) rates of decision errors, treatment costs and adverse clinical events among treated patients remain largely unchanged despite the altered practice styles.
Keywords: C23; D61; D91; I11; I18; O33; 330; Practice Style; Environment; Peers; Quality of Care